2020
DOI: 10.1021/acsami.0c04366
|View full text |Cite
|
Sign up to set email alerts
|

Superwicking on Nanoporous Micropillared Surfaces

Abstract: Engineering surfaces with excellent wicking properties is of critical importance to a wide range of applications. Here, we report a facile method to create superhydrophilic nanoporous micropillared surfaces of silicon and their applicability to superwicking. Nanopores with a good control of the pore depth are realized over the entire surface of three-dimensional micropillar structures by electrochemical etching in hydrofluoric acid. After rinsing in hydrogen peroxide, the nanoporous micropillared surface shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…e) Comparison of the ECE temperature change of PMW ceramic with representative FE/AFE bulk materials under different temperatures. : Pb(Zr,Ti)O 3 ‐based bulks, [ 19,20,30,31,39–41,58 ] [: BaTiO 3 ‐based bulks, [ 11,42–47 ] : Na 0.5 Bi 0.5 TiO 3 ‐based bulks, [ 51–56 ] : (K,Nb)NbO 3 ‐based bulks, [ 15,48–50 ] : BiFeO 3 ‐based bulk, [ 57 ] : PMW ceramic. f) The maximum entropy changes and corresponding temperature changes of positive and negative ECEs under different electric fields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Comparison of the ECE temperature change of PMW ceramic with representative FE/AFE bulk materials under different temperatures. : Pb(Zr,Ti)O 3 ‐based bulks, [ 19,20,30,31,39–41,58 ] [: BaTiO 3 ‐based bulks, [ 11,42–47 ] : Na 0.5 Bi 0.5 TiO 3 ‐based bulks, [ 51–56 ] : (K,Nb)NbO 3 ‐based bulks, [ 15,48–50 ] : BiFeO 3 ‐based bulk, [ 57 ] : PMW ceramic. f) The maximum entropy changes and corresponding temperature changes of positive and negative ECEs under different electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5e compares the ECE Δ T and corresponding transition temperatures of typical FE/AFE bulk materials studied in the literature. [ 11,15,19,20,30,31,39–58 ] Similar caution applies to calculations of false negative ECEs. [ 20,37,38,52,59 ] There are very few examples in the literature of FE materials with giant ECE near room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical structures reported recently include nanocactus arrays, 35 micropillars with nanowires, 36 nanorods on micropillars, 37 and nanoporous micropillared surfaces. 38 The hierarchical structures show faster wicking speed compared to single-scaled structures, which is due to the additional capillary pressure by nanostructures and the minimized viscous resistances by microstructures. For example, Wang et al 36 found that the wicking speed of three-dimensional hierarchical structure with intermediate nanowire lengths was faster than that of structures without nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The additional viscous resistance became significant when nanowire height approached half of the micropillar spacing of hierarchical surfaces, which is because the wicking channels were narrowed down by nanowires. In order to reduce the viscous resistance introduced by nanostructure, Zheng et al 38 reported that the nanoporous micropillared surfaces, as opposed to nanowires, can maintain the liquid channels without reducing the width of channels. Nanopores have disconnected internal spaces which are distinct from the nanowires and nanopillars conventionally employed in hierarchical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multiple local minima in the system energy and thus metastable equilibrium states can be induced by the micro/nanostructure of a surface, which has been found to substantially hinder or even prevent wetting processes such as spontaneous or forced spreading, capillary imbibition, or interfacial adsorption. The dynamics of capillary imbibition can be reasonably well described by considering capillary pressure and viscous hydrodynamic resistance, as in the conventional Lucas-Washburn equation, for the case of macroscopically smooth and chemically homogeneous surfaces when the system is sufficiently far from equilibrium. However, capillary imbibition on micro/nanostructured surfaces presents nontrivial dynamic behaviors that are not accounted for by conventional models due to the presence of metastable states and thermally activated processes induced by physical and/or chemical heterogeneities of wetted micro/nanopatterned surfaces. Engineering the micro/nanostructure of a surface can thus provide diverse pathways to control the static and dynamic wetting behavior of different liquids such as water and oil.…”
Section: Introductionmentioning
confidence: 99%